A167 AN ANALYSIS OF TREATMENT UPTAKE AND EFFICACY USING ALL-ORAL DIRECT-ACTING ANTIVIRAL (DAA) THERAPY IN HCV-INFECTED PEOPLE WHO INJECT DRUGS (PWID). (1st March 2018) - Shahi, R; Kiani, G; Alimohammadi, A; Raycraft, T; Singh, A; Conway, B
Abstract: Background: Approximately 300, 000 Canadians are infected with Hepatitis C (HCV), including over 60, 000 British Columbians. People who inject drugs (PWID) account for over 50% of HCV infection cases in Canada. Historically, many medical professionals have considered PWID unsuitable candidates for HCV therapy due to concerns about adherence and reinfection after successful treatment. However, the availability of all-oral regimens has led to increased efficacy with improved tolerability and shorter treatment duration. This may represent a unique opportunity to engage HCV-infected PWID more effectively than was possible with interferon-based regimens. This study seeks to assess the efficacy of all-oral HCV therapies among PWID and provide a rationale for enhanced programs in this key population. Aims: Our study seeks to assess the efficacy of all-oral HCV therapies among PWID and provide a rationale for enhanced programs in this key population. Methods: A retrospective cohort analysis was performed on all HCV-infected patients who were treated at a tertiary clinic in downtown Vancouver and had a history of recent and ongoing injection drug use. HCV therapy was administered in the context of a program to address relevant medical, social, psychologic and addiction-related concerns. Appropriate HCV treatment regimens were chosen and follow-up visits (at weeks 2, 4, 6, 8, 10, 12, and/or 24 weeks) were scheduled. The primary outcome of the analysis was achievement of a sustained virologic response (SVR). Results: To date, 50 active PWID received and completed all-oral HCV regimens. Key demographic variables include: mean age 52.4 (34–75) years, 74% male, 40% on opiate substitution therapy, 62%/66%/46% using heroin/cocaine/other stimulants. SVR was achieved in 44 (88%) cases; 4 patients (8%) exhibited virologic relapse and 0 (0%) were re-infected after a median 18 month follow-up period. The 4 patients with virologic relapse were on Sofosbuvir-based regimens - 1 patient with genotype 2a/2c (with Ribavirin), 2 patients with genotype 3a (with NS5A Inhibitor), and 1 patient with genotype 1a (with NS5A Inhibitor). Conclusions: Although barriers to care exist among PWID, the availability of all-oral regimens represents an important advance to address them. High efficacy can be achieved in this vulnerable population, and it may be that post-treatment re-infection rates will be lower than might have been expected, especially with delivery of care and long-term follow-up within multidisciplinary programs such as ours. There is a need to establish a national cohort of HCV-infected PWID to optimize the parameters of engagement in medical care, provision of HCV therapy and long-term follow-up in this population. Funding Agencies: None